Comparison of LDL fatty acid and carotenoid concentrations and oxidative resistance of LDL in volunteers from countries with different rates of cardiovascular disease - Wright, Anthony J. A.; Southon, Susan; Chopra, Mridula; Meyer-Wenger, Anita; Moser, Ulrich; Granado, Fernando; Olmedilla, Begoña; Corridan, Bernice; Hinninger, Isabelle; Roussel, Anne-Marie; van den Berg, Henk; Thurnham, David I. (British journal of nutrition, 2002)
Within Europe there are differences in cardiovascular disease (CVD) risk between countries and this might be related to dietary habits. Oxidative modification of LDL is suggested to increase the risk of CVD and both the fatty acid and antioxidant content of LDL can affect its oxidation. In the present study, concentration of LDL fatty acid and antioxidant micronutrients (tocopherols and carotenoids) and ex vivo oxidative resistance of LDL (lag phase) was compared in volunteers from five countries with different fruit and vegetable intakes and reported rates of CVD. Eighty volunteers (forty males, forty females per centre), age range 25–45 years, were recruited from France, Northern Ireland, UK, Republic of Ireland, The Netherlands, and Spain, and their LDL composition and lag phase were measured. There were some differences in LDL carotenoid and α-tocopherol concentrations between countries. α-Tocopherol was low and β- + γ-tocopherol were high (P<0·001) in the Dutch subjects. β-Carotene concentrations were significantly different between the French and Spanish volunteers, with French showing the highest and Spanish the lowest concentration. LDL lycopene was not different between centres in contrast to lutein, which was highest in French (twofold that in the Dutch and Spanish and threefold that in Northern Ireland and the Republic of Ireland, P<0·001). However absolute LDL saturated, monounsaturated, polyunsaturated and total unsaturated fatty acid concentrations were different between countries (P<0·001, total unsaturated highest in Northern Ireland) there was little difference in unsaturated:saturated fatty acid concentration ratios and no difference in polyunsaturated:saturated fatty acid concentration ratios. LDL from the Republic of Ireland (a region with a high rate of CVD) had greater resistance to Cu-stimulated oxidation than samples obtained from volunteers in other countries. In conclusion, LDL composition did not predict resistance to Cu-stimulated oxidation, nor is there evidence that LDL from volunteers in countries with lower rates of CVD have greater resistance to oxidation.